Analysis of Fatty Acid Composition Using GC-MS Method and Antibacterial Activity Test of n-Hexane Extract from Petai Seeds (Parkia speciosa Hassk.) - Marpaung, Lamek; Sinaga, Rio Maretanto (Talenta Publisher, 2022)
Analysis of fatty acid composition using GC-MS method and antibacterial activity test of n-hexane extract from Petai seed (Parkia speciosa Hassk.) has been performed. Fatty acid was extracted from petai seed by maceration method using n-hexane solvent to produce n-hexane extract converted into fatty acid methyl ester through a methanolysis reaction. Then fatty acid composition was analyzed using the GC-MS method. The result of GC-MS analysis showed that the fatty acid composition found in 760 gr petai seeds which produced 11.16 g of fatty acids, was 1.0088 gr palmitic acid methyl ester (9.04%), 1.2700 gr linoleic acid methyl ester (11.38 %), 7.3556 gr oleic acid methyl ester (65.91%) and 1.4887 gr stearic acid methyl ester (13.34%). The antibacterial activity test showed that all concentrations of n-hexane extracts of 50 mg/ml, 150 mg/ml, and 250 mg/ml tested were able to inhibit the growth of E. coli and S. aureus bacteria in n-hexane extract, wherein the inhibited zone by the n-hexane extract is included in the weak category (â‰¤14 mm) except at the concentration of 250 mg/ml in the S. aureus test bacteria belonging to the medium type (15-19 mm).